Certified Reference Material for the Quantification of Phthalates in Polyvinyl Chloride Resin (NMIJ CRM 8152). (12th April 2021) - Hanari, Nobuyasu; Orihara, Yukari; Matsuyama, Shigetomo
Abstract: Phthalates are primary industrial chemicals used as polyvinyl chloride (PVC) plasticizers. However, certain phthalates are controlled as restricted substances listed under Annex II of Directive 2011/65/EU, (EU)2015/863. Since an accurate quantification of phthalates is essential to monitoring their concentration levels, quality assurance during their analyses using certified reference materials (CRMs) is required. A PVC CRM for the quantification of phthalates (NMIJ CRM 8152) was provided by the National Metrology Institute of Japan. This CRM was in the form of grayish-white pellets (3-mm diameter × 3-mm length). The analytical procedures adopted were isotope-dilution mass spectrometry, which was the primary method of measurement, and gas chromatography/mass spectrometry; these procedures were optimized and applied to the characterization. The mass fractions of five target phthalates calculated using the mean values were determined as the certified values of the CRM. The relative standard uncertainties attributed to the certification were combined, e.g., those for the characterization, inhomogeneity, and instability. The mass fractions of five phthalates were certified, and those of three phthalates and one adipate were acquired and are reported as technical information. The CRM is shown to be applicable to assessing the validity of analytical methods during the quantification of phthalates in PVC resin and similar materials.